Association between obesity, quality of life, physical activity and health service utilization in primary care patients with osteoarthritis - Herman Katja; Grol Richard; Rosemann Thomas; Wensing Michel; Szecsenyi Joachim (BMC, 2008)
Abstract Objective To assess the association of obesity with quality of life, health service utilization and physical activity in a large sample of primary care patients with osteoarthritis (OA). Methods Data were retrieved from the PraxArt project, representing a cohort of 1021 primary care patients with OA. In 978 patients, height and weight were measured and the Body Mass Index (BMI) was calculated. The AIMS2-SF was used to assess quality of life (QoL). Data about health service utilization (HSU) were retrieved by means of patients' medical files. Concomitant depression was assessed by means of the Patient Health Questionnaire (PHQ-9). Patients were grouped into normal weight, overweight and obese according to the definition of the WHO and compared by means of analysis of covariance (ANCOVA). Results Obese and overweight persons achieved significantly higher scores on the AIMS2-SF lower body scale, the symptom, the affect and the work scale, indicating an increased burden by OA. The PHQ-9 score increased significantly over the three weight-groups, indicating a positive association of BMI and depression. With increasing BMI, the number of comorbidities increased and physical activity decreased significantly. After controlling for covariates, contacts to orthopaedics and performed x-rays remained significantly higher in obese patients, but not contacts to general practitioners. Conclusion The results display a strong association of QoL and BMI, resulting in increased use of the health care system. Thus, the study emphasizes the need for appropriate approaches in primary care to break the vicious circle of overweight, depression, decreasing physical inactivity and decreasing QoL.